Kesadaran Toleransi melalui Pelestarian Cagar Budaya di Situs Srigading - Arifin, Fadhillah Irgi Farros (Yayasan Alpatih Harapan Semesta, 2024)
The importance of Srigading Temple as a Hindu worship site for the God Brahma is a challenge in its preservation. This article discusses the promotion of tolerance awareness through the preservation of cultural heritage at the Srigading Site, located in Malang, East Java. Using literature studies and surveys, the research identifies gaps in awareness and commitment to cultural preservation. The findings underscore the importance of education and collaboration among communities, local authorities, and stakeholders to sustain the site's cultural and historical value for future generations.